2013
DOI: 10.1002/jemt.22306
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study by computed radiography, histology, and scanning electron microscopy of the articular cartilage of normal goats and in chronic infection with caprine arthritis‐encephalitis virus

Abstract: In the northeast of Brazil, caprine arthritis-encephalitis (CAE) is one of the key reasons for herd productivity decreasing that result in considerable economic losses. A comparative study was carried out using computed radiography (CR), histological analysis (HA), and scanning electronic microscopy (SEM) of the joints of CAE infected and normal goats. Humerus head surface of positive animals presented reduced joint space, increased bone density, and signs of degenerative joint disease (DJD). The carpal joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Sousa et al in 2014 (22) agreed also with this study and noted a chronic systemic auto-immune inflammatory disease involving the breakdown of cartilage and adjacent bone tissue. Also they noted irregular and folded patterns on the joint surface that distinguished the limits between areas of normal and affected cartilage.…”
Section: Discussionsupporting
confidence: 87%
“…Sousa et al in 2014 (22) agreed also with this study and noted a chronic systemic auto-immune inflammatory disease involving the breakdown of cartilage and adjacent bone tissue. Also they noted irregular and folded patterns on the joint surface that distinguished the limits between areas of normal and affected cartilage.…”
Section: Discussionsupporting
confidence: 87%
“…In addition chondrocytes showed centrally located nuclei. Staining of chondrocytes revealed that they had a fine granular appearance that contained little vacuoles and were surrounded by extracellular matrix [ 26 ]. As reported previously, TEM micrographs revealed that the extracellular matrix in articular cartilage showed a fibrillary flatwork that was composed of denser and thicker fibrils.…”
Section: Discussionmentioning
confidence: 99%
“…Sousa et al (2014) studied the morphology of joints from healthy goats and those infected with CAE; they noted that the shoulder joint showed a reduction in joint space, an increase in bone density, and other signs of degenerative joint disease. These authors also observed that the carpus joint was not morphologically affected, but the tarsal joint was dramatically affected; no joint space could be seen, an increase in periarticular density was noted, along with swelling and bone sclerosis.…”
Section: A B Discussionmentioning
confidence: 99%